Technical specifications on harmonised monitoring of antimicrobial resistance in zoonotic and indicator bacteria from food‐producing animals and food. (5th June 2019) - ,; Aerts, Marc; Battisti, Antonio; Hendriksen, René; Kempf, Isabelle; Teale, Christopher; Tenhagen, Bernd‐Alois; Veldman, Kees; Wasyl, Dariusz; Guerra, Beatriz; Liébana, Ernesto; Thomas‐López, Daniel; et al.
Abstract: Proposals to update the harmonised monitoring and reporting of antimicrobial resistance (AMR) from a public health perspective in Salmonella, Campylobacter coli, Campylobacter jejuni, Escherichia coli, Enterococcus faecalis, Enterococcus faecium and methicillin‐resistant Staphylococcus aureus (MRSA) from food‐producing animals and derived meat in the EU are presented in this report, accounting for recent trends in AMR, data collection needs and new scientific developments. Phenotypic monitoring of AMR in bacterial isolates, using microdilution methods for testing susceptibility and interpreting resistance using epidemiological cut‐off values is reinforced, including further characterisation of those isolates of E. coli and Salmonella showing resistance to extended‐spectrum cephalosporins and carbapenems, as well as the specific monitoring of ESBL/AmpC/carbapenemase‐producing E. coli . Combinations of bacterial species, food‐producing animals and meat, as well as antimicrobial panels have been reviewed and adapted, where deemed necessary. Considering differing sample sizes, numerical simulations have been performed to evaluate the related statistical power available for assessing occurrence and temporal trends in resistance, with a predetermined accuracy, to support the choice of harmonised sample size. Randomised sampling procedures, based on a generic proportionate stratified sampling process, have been reviewed and reinforced. Proposals to improve the harmonisation of monitoring of prevalence, genetic diversity and AMR in MRSA are presented. It is suggested to complement routine monitoring with specific cross‐sectional surveys on MRSA in pigs and on AMR in bacteria from seafood and the environment. Whole genome sequencing (WGS) of isolates obtained from the specific monitoring of ESBL/AmpC/carbapenemase‐producing E. coli is strongly advocated to be implemented, on a voluntary basis, over the validity period of the next legislation, with possible mandatory implementation by the end of the period; the gene sequences encoding for ESBL/AmpC/carbapenemases being reported to EFSA. Harmonised protocols for WGS analysis/interpretation and external quality assurance programmes are planned to be provided by the EU‐Reference Laboratory on AMR.